Platelet phosphatidylserine exposure and procoagulant activity in clotting whole blood – different effects of collagen, TRAP and calcium ionophore A23187 - Ramström, Sofia; Rånby, Mats; Lindahl, Tomas L. (Thrombosis and Haemostasis, 2003)
We have studied the effects of different platelet agonists on phosphatidylserine (PS) exposure and clotting times in blood without anticoagulants. Similar reductions in clotting time were obtained for collagen, TRAP-6 or calcium ionophore A23187 (50 μmol/L), in spite of huge differences in PS expression [6.7 ± 2.4%, 2.3 ± 0.5% and 99.9 ± 0.1%, respectively (mean ± SD, n = 5)]. Furthermore, the clotting times were much longer for samples with A23187 exposing the same amounts of PS as samples with collagen or TRAP-6. Annexin V reversed the clotting time reduction, but could not prevent coagulation. Addition of phospholipid vesicles containing 20% PS neither affected the clotting times nor induced clotting in recalcified, platelet-free plasma.We conclude that platelet PS exposure is necessary, but not sufficient, for the coagulation amplification observed when platelets are stimulated via physiological receptors in a whole blood environment.
Keywords: Hemostasis; blood platelets; platelet activation; platelet procoagulant activity; platelet factor 3